IMPACTOF COVID- 19 PANDEMIC ON DIGITAL PAYMENTS IN INDIA: A STUDY - Saleem, Dr. Shahrukh; Sreekanth, Mr. B.; Gangisetty, Dr. N. (The journal of contemporary issues in business and government, 2022)
The aim of this research paper is to study factors impacting digital payments in India during the Covid-19 Pandemic. The paper has used Factor Analysis, Confirmatory Factor Analysis (CFA), Multiple linear Regression, Chi Square Test, T-test ,ANOVA and descriptive statistics for the purpose of analysis. The paper is analysed on a sample 300 respondents and data was collected through a structured questionnaire. This study proposed the variables affecting the digital payments during the pandemic after thorough analysis. The study found that there was a spike in various digital payments usage for the customers during the pandemic due to various safety concerns and lockdowns imposed by the government.The results show high usage of various digital banking services by the customers during the pandemic.